Collaborative Qur’anic Transmission in the Ngaji Tradition: The Case of Peripheral Muslim Community in Nusa Pandau, Indonesia - Hamdan, Ali; Miski; Faisal Mahmoud Adam Ibrahim (Faculty of Ushuluddin and Religious Study, Universitas Islam Negeri Raden Intan Lampung, 2026)
How is the Qur’an transmitted within geographically peripheral Muslim communities? This article examines the dynamics of Qur’anic transmission within the ngaji tradition in Nusa Pandau, a remote Muslim community along the Melawi River in West Kalimantan, Indonesia. Drawing on qualitative field research with a socio-historical approach, the study is based on observation and in-depth interviews with Qur’anic teachers, students, and local religious actors involved in the transmission process. The findings demonstrate that Qur’anic transmission in Nusa Pandau operates collaboratively through multiple religious agents rather than through a single dominant authority. Within the ngaji tradition, transmission encompasses not only Qur’anic recitation but also the transmission of religious values, aesthetic practices of tilawah, and interpretive meanings embedded in communal religious activities. The study further reveals that Qur’anic transmission in this peripheral Muslim community developed through interconnected networks linking local traditions with Javanese and Sumatran Qur’anic pedagogical lineages, particularly through the circulation of the Baghdadiyah method and sanad-based learning practices. These findings suggest that geographical remoteness does not isolate Muslim communities from broader Qur’anic networks; instead, it encourages adaptive, collaborative, and non-contestative forms of religious authority and Qur’anic learning. [Bagaimana transmisi Al-Qur’an berlangsung dalam komunitas Muslim yang berada di wilayah geografis perifer? Artikel ini mengkaji dinamika transmisi Al-Qur’an dalam tradisi ngaji di Nusa Pandau, sebuah komunitas Muslim terpencil di tepian Sungai Melawi, Kalimantan Barat, Indonesia. Penelitian ini merupakan penelitian lapangan kualitatif dengan pendekatan sosio-historis yang didasarkan pada observasi dan wawancara mendalam terhadap guru ngaji, murid, dan aktor-aktor keagamaan lokal yang terlibat dalam proses transmisi Al-Qur’an. Temuan penelitian menunjukkan bahwa transmisi Al-Qur’an di Nusa Pandau berlangsung secara kolaboratif melalui banyak agen keagamaan, bukan melalui satu otoritas tunggal yang dominan. Dalam tradisi ngaji, transmisi tidak hanya mencakup bacaan Al-Qur’an, tetapi juga transmisi nilai-nilai keagamaan, praktik estetika tilawah, dan pemaknaan ayat-ayat Al-Qur’an yang terintegrasi dalam aktivitas keagamaan komunal. Penelitian ini juga menunjukkan bahwa transmisi Al-Qur’an di komunitas Muslim perifer tersebut berkembang melalui jejaring yang saling terhubung antara tradisi lokal dengan genealogi pedagogi Al-Qur’an dari Jawa dan Sumatra, terutama melalui sirkulasi metode Baghdadiyah dan praktik pembelajaran berbasis sanad. Temuan ini menegaskan bahwa keterpencilan geografis tidak mengisolasi komunitas Muslim dari jejaring Al-Qur’an yang lebih luas, tetapi justru mendorong terbentuknya model otoritas keagamaan dan pembelajaran Al-Qur’an yang adaptif, kolaboratif, dan non-kontestatif.]